Fibre structure characterisation of injection moulded short fibre-reinforced polymers by X-ray scatter dark field tomography. (April 2015) - Hannesschläger, Christian; Revol, Vincent; Plank, Bernhard; Salaberger, Dietmar; Kastner, Johann
Abstract: X-ray scatter dark field imaging (SDFI) tomography was used to investigate the glass fibre orientation of short fibre-reinforced polymers (SFRPs). The fibre orientation of fibre-reinforced polymers is decisive for the mechanical strength of injection-moulded parts. For this paper four different positions, with volumes along the melt flow and with weld lines, of an injection-moulded part were investigated with SDFI computed tomography with a voxel size of (43 μm) 3 and absorption-based high resolution X-ray computed tomography (XCT) with a voxel size of (6.5 μm) 3 . The results of the SDFI computed tomography are compared with the fibre orientation to investigate the dependence of the SDFI signal on fibre orientation. The exact fibre orientation was determined by evaluation of the high resolution absorption XCT data. In particular, it is shown that the weld line and areas with different fibre orientations can be characterised by SDFI even at a voxel size of (43 μm) 3 and that fibre orientation properties can be detected.